2016
DOI: 10.1111/gtc.12451
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient‐dependent increased dendritic arborization of somatosensory neurons

Abstract: Suboptimal nutrition imposes developmental constraints on infant animals, which marshal adaptive responses to eventually become mature adults. Such responses are mounted at multiple levels from systemic to cellular. At the cellular level, the underlying mechanisms of cell proliferation control have been intensively studied. However, less is known about how growth of postmitotic and morphologically complex cells, such as neurons, is controlled by nutritional status. We address this question using Class I and Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 64 publications
(117 reference statements)
2
28
0
Order By: Relevance
“…We asked whether nutrient stress also impacts dendritic growth of C1da and C3da neurons. Consistent with the previous report by Watanabe et al (Watanabe et al, 2017), the yeast concentration did not have obvious effects on the total dendrite length of C1da neuron ddaE (Figures 7A-7C). However, nutrient stress stimulated the dendritic growth of C3da neurons ddaA and ddaF: the total dendrite length increased by 40% and 32%, respectively; the total terminal dendrite length increased by 61% and 46%, respectively; the terminal branch numbers increased by 47% and 58%, respectively (Figures 7D-7H).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…We asked whether nutrient stress also impacts dendritic growth of C1da and C3da neurons. Consistent with the previous report by Watanabe et al (Watanabe et al, 2017), the yeast concentration did not have obvious effects on the total dendrite length of C1da neuron ddaE (Figures 7A-7C). However, nutrient stress stimulated the dendritic growth of C3da neurons ddaA and ddaF: the total dendrite length increased by 40% and 32%, respectively; the total terminal dendrite length increased by 61% and 46%, respectively; the terminal branch numbers increased by 47% and 58%, respectively (Figures 7D-7H).…”
Section: Resultssupporting
confidence: 93%
“…A recent study by Watanabe et al (2017) reported that C4da neurons were hyperarborized when Drosophila larvae developed on a low yeast diet that restricts the availability of lipids and amino acids, an interesting and surprising finding that agrees with our independent observation. In our experiments, we examined larvae reared in high yeast (HY, 8% yeast) and low yeast (LY, 1% yeast) media that otherwise contained only glucose as a carbon source.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Input files consisted of original image data (8‐bit and 1,024 × 1,024 pixels) of larval class IV neurons on HYD or LYD (8% and 0.8% Y diet in Watanabe et al, , respectively) and a region of interest (ROI) of each image. We used Adobe Photoshop to define the ROI by drawing a path using a pen tool and filling the path with red color.…”
Section: Methodsmentioning
confidence: 99%
“…Marker strains employed were ppk-GAL4 UAS-mCD8:GFP (Grueber et al, 2007) and Gr28b.c-GAL4 UAS-mCD8:GFP (Xiang et al, 2010). Preparing diets and rearing flies were performed as described (Watanabe et al, 2017). All of the crosses and experiments were conducted under noncrowded conditions at 25°C.…”
Section: Training Datasetsmentioning
confidence: 99%